Comparación de las terapias detartraje y alisado radicular, irrigación subgingival con clorhexidina y cepacol en el tratamiento de la periodontitis marginal crónica incipiente generalizada: estudio piloto - Arboleda-O., Maria Mercedes; Aristizabal-G., Andres; Becerra-Santos, Fabio (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The present study was designed as a pilot study, with the purpose of comparing the effects of various subgingival irrigation substances in combination with scaling- and rootplanning- in non - surgical periodontal therapy, and therefore evaluate the periodontal tissues response. For that effect tarzpatierzts were chosen from both sexes and in ages between 19 and 50 years, with diagnosis of incipient adult marginal periodontitis. Baseline records were taken before scaling and root planning applying clinical attachment level, gingival index, plaque index and percentage of bleedin g sites; repeating-records at the second, fourth and sixth months to evaluate treatment efficacy. Even though reduction in all indexes was found between cero and six months with all therapies only the gingival index showed a positive statistical significant correladon.